Influence of Moisture and Hydrogen Peroxide Fiber Treatment on the Flexural Properties of Polypropylene Composites Reinforced with Unsmoked Cigarette Butts - de Souza, Milena Chanes [UNESP]; Moroz, Ivan [UNESP]; Cesarino, Ivana [UNESP]; Bronzato, Giovana Roberta Francisco [UNESP]; Reis, Victor Angelo Cavalari Arantes dos [UNESP]; de Carvalho Brito, Lucas Balieiro [UNESP]; Zanzini, Murilo Gibbin [UNESP]; Leão, Alcides Lopes [UNESP] (Wiley, 2022)
Smuggled cigarettes are seized around the world, and a correct destination is needed for this material. In this context, the Federal Revenue of Brazil (RFB) has created Ordinance n°59 of 2019 on the destination of contraband cargo seizures, to which this manuscript aims to propose a use with greater added value. The influence of two factors on the flexural properties of composite samples are studied as follows: i) the influence of prior hydrogen peroxide treatment executed on the cigarette butts (CBs), tested in composite samples made with 50% Polypropylene (PP) and 50% CBs in wt%; and ii) the influence of moisture on composites composed of 60% PP and 40% CBs in wt%, after up to 72 h immersed in water. The fiber treatment has not caused significant reduction of flexural properties in the produced composites, and all composite samples with moisture have showed greater flexural strength (FS) and flexural modulus (FM) than the dry sample. However, these bending properties can decrease as the moisture increases, so further studies are encouraged. It is demonstrated that these composites are feasible to produce, may be used in moist environments in flexural stresses and allow for fiber hydrogen peroxide treatment without significant reduction in flexural properties.
Keywords: cigarette butts (CBs); composites; moisture absorption; poly(propylene) (PP); treatment